The Influence of Different Social Roles Activation on Women’s Financial and Consumer Choices - Sekścińska, Katarzyna; Trzcińska, Agata; Maison, Dominika A. (Frontiers in Psychology, 2016)
In recent times, the changes occurring in the social role of women and men have been observed. Traditionally, the dominating social role of the woman was as housewife, and that of the man was focused on work and family maintenance. Nowadays, the social role of women is evolving in the direction of taking a profession, while increasingly men are taking care of the household. The main goal of the studies presented here was to verify how the activation of different social roles (traditional or nontraditional) may be reflected in women’s financial and consumer choices. Three experimental studies were conducted. In the first study (n= 195 females), three different social roles of women – professional (nontraditional), housewife (traditional) and neutral (control) – were activated. The results showed that activating women’s nontraditional social role increased their tendency to invest and decreased their propensity to save money compared to the activation of the traditional or neutral social role. The goal of the second study (n=196 females) was to check whether, despite there being no differences in the level of consumption in the first study, can any differences be observed in the preference for the type of products chosen for consumption. The results showed that activating the nontraditional social role raised the propensity to spend funds on products and services for individual use and reduced the willingness to buy goods for collective use (shared with other members of the household). The purpose of the third study (n=90 females) was to examine how different images of women appearing in advertisements may affect women’s judgments of the advertised product. Women who watched the ad with woman in the nontraditional social role estimated the product quality, look, color and price higher that participants exposed to the advertisement presenting the woman in traditional or neutral social role. The present studies give some evidence that the new, nontraditional social role of women that is often presented in the media may affect women’s everyday financial choices and judgments of products.